2010
DOI: 10.1098/rspb.2010.1959
|View full text |Cite
|
Sign up to set email alerts
|

Ant association facilitates the evolution of diet breadth in a lycaenid butterfly

Abstract: The role of mutualistic interactions in adaptive diversification has not been thoroughly examined. Lycaenid butterflies provide excellent systems for exploring mutualistic interactions, as more than half of this family is known to use ants as a resource in interactions that range from parasitism to mutualism. We investigate the hypothesis that protection from predators offered to caterpillars by ants might facilitate host-range evolution. Specifically, experiments with the butterfly Lycaeides melissa investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…Savignano () found that the presence of ants did not reduce parasitism but did reduce predation in Lycaeides samuelis (formerly L. melissa samuelis ; Forister et al , ). Combined with the results from Savignano () and a previous study from one of our focal sites (Forister et al , ), it seems likely that the presence of ants reduces predation, but not parasitism in L. melissa .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Savignano () found that the presence of ants did not reduce parasitism but did reduce predation in Lycaeides samuelis (formerly L. melissa samuelis ; Forister et al , ). Combined with the results from Savignano () and a previous study from one of our focal sites (Forister et al , ), it seems likely that the presence of ants reduces predation, but not parasitism in L. melissa .…”
Section: Discussionsupporting
confidence: 78%
“…Lycaeides melissa caterpillars are facultatively myrmecophilous, providing secretions rich in sugars and amino acids that attract the attention of ants that tend and presumably protect caterpillars. Forister et al () found that the presence of ants reduced rates of attack by generalist predators of L. melissa on the novel host alfalfa, but not on the native host A. canadensis . Other studies have shown that ants can also protect lycaenids from parasitoids (Pierce & Mead, ; Pierce & Easteal, ; Weeks, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Forister et al . ), with limited dispersal among localities (i.e. dispersal beyond 500 m is rare; U.S.…”
Section: Methodsmentioning
confidence: 92%
“…In a few well‐studied examples, hosts shifts involving exotic plants have resulted in speciation (e.g., Rhagoletis flies shifting from hawthorn to apple trees; Feder 1998; Feder and Forbes 2008), the evolution of feeding morphology (e.g., Leptocoris bugs adapting to introduced hosts in the Sapindaceae; Carroll 2008; Carroll et al 2005a), and shifts in oviposition behavior (e.g., Euphydryas butterflies and exotic Plantago hosts; Singer et al 1993, 2008). A shift to an exotic host has also been associated with an escape from natural enemies ( Papilio machaon aliaska caterpillars on novel Asteraceae hosts; Murphy 2004), as well as an increased reliance on a protection mutualism ( Lycaeides melissa caterpillars with ants on alfalfa; Forister et al 2011). Outside these detailed studies, we have much to learn about the frequency with which native insects use exotic plants, the potential for host shifts, and the conditions which either constrain or promote the colonization of exotic hosts (Thompson 1998; Strauss et al 2006).…”
mentioning
confidence: 99%